Mollaret's Meningitis: A Case Report and Review of the Literature (TAJ: Journal of Teachers Association, 2009)
Mollaret's meningitis is defined as a benign recurrent aseptic meningitis characterized by three to ten episodes of fever and signs of meningeal irritation lasting between 2 to 5 days, associated with spontaneous recovery. Mollaret in 1944 described this rare form of self limiting aseptic recurrent benign meningitis. It is an extremely rare condition. Till 2002 approximately 50 cases of recurrent HSV meningitis have been described in the United States and in Europe. Here a report of a patient with recurrent meningitis, which resembles the criteria of Mollaret's Meningitis, is presented.   doi: 10.3329/taj.v17i1.3489 TAJ 2004; 17(1) : 41-46